Uncovering QTLs for uppermost internode length and panicle exsertion in rice (Oryza sativa L.) - Harshitha, Bheemapura Shivakumar; Singh, Vikram Jeet; Nandakumar, Shekharappa; Shekhawat, Sonu; Dixit, Brijesh Kumar; Ragi, Shridhar; Saran, Deepak; Vinod, Kunnummal Kurungara; Krishnan, Subbaiyan Gopal; Ellur, Ranjith Kumar; Nagarajan, Mariappan; Bollinedi, Haritha; et al. (Frontiers in Sustainable Food Systems, 2024)
Uppermost internode length and panicle exsertion are the two important traits that contribute significantly to increased yield in rice. The present study was conducted using recombinant inbred lines (RILs) comprising of 201 lines derived from RTN10B and IRG213. These RILs were evaluated at three different locations namely, Delhi, Karnal, and Aduthurai, and we report mapping of quantitative trait loci (QTLs) for uppermost internode length and panicle exsertion ratio, together with QTLs for plant height, tiller number, length of second internode, length of third internode, length from flag leaf to panicle tip, panicle length. Mapping was done using a custom microsatellite linkage map constructed for the population, having a total span of 2077.1 cM with 104 markers. A total of 22 QTLs were identified for different traits, among which 19 were found distributed in four hotspots. A total of 11 major effect QTLs and 11 minor effect QTLs were identified for various internode length related traits. Among the four QTLs identified for PFL, three QTLs, qPFL1.1, qPFL1.2, and qPFL2.1, co-localised with the previous reported QTL while qPFL8.1 is a novel QTL. A major QTL hotspot was identified on chromosome 1, lying at the marker interval of RM12055-RM320. The size of the major QTL hotspot on chromosome 1 is 1.4 Mb and possess total seven HEs for PER, PFL, PH, PL, UIL, SIL, and TIL. Based on the in-silico analysis of the major QTL hotspot on chromosome 1, we were able to identify 15 putative candidate genes associated with internode length and panicle-related traits. Further, narrowing the genomic region through fine mapping of marker intervals facilitates the identification of candidate genes to enable more precise marker-assisted selection for uppermost internode length and panicle exsertion.